FROM THE HISTORY OF TASHKENT STATE LAW UNIVERSITY - Amirov Elbek (Scholar Express Journals, 2022)
As it is known from society and human development, the formation and development of legal science and education was influenced by the needs of the society and the state for fair law and the need to systematize the current legislation. The secular legal education of our country has a glorious, tradition-rich history. The foundation of secular legal education in our country was established on April 21, 1918, with the introduction of the Faculty of Socio-Economics with a legal department in Turkestan People's University
Keywords: Turkey; Cabinet of Ministers; legal field; scientific-theoretical analysis